Identification and functional characterisation of a novel surface protein complex of Lactobacillus rhamnosus : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Microbiology and Genetics at Massey University, Manawatu Campus, New Zealand - Wen, Wesley Xingli (Massey University, 2016)
Proteins are the most diverse structures on bacterial surfaces; hence they are candidates for species- and strain-specific interactions of bacteria with the host, environment and other microorganisms. In probiotic bacteria, some surface and secreted proteins mediate interactions with the host and may consequently contribute to the health-promoting effects. However, a limited fraction of surface-associated proteins from probiotic bacteria have been functionally characterised to date. A secreted protein of Lactobacillus rhamnosus HN001, SpcA, containing two bacterial immunoglobulin-like domains type 3 (Big-3) and a domain distantly related to plant pathogen response domain 1 (PR-1-like), was previously shown to bind to HN001 cells, however the nature of its ligand on the surface of the cells was unknown. In this study, a series of binding assays first demonstrated that SpcA binds to a cell wall anchored protein of HN001. Next, the SpcA-“docking” protein, named SpcB, was identified using phage display. SpcB is a 3275-residue cell-surface protein that has all the features of large glycosylated serine-rich adhesins/fibrils from Gram-positive bacteria, including the hallmark glycoprotein signal sequence motif KxYKxGKxW and the cell wall anchor motif LPxTG. The spcA and spcB genes are located in a gene cluster, spcBCDA, which is present in 94 out of 100 strains of L. rhamnosus species and some strains of L. casei and L. paracasei whose genome sequences have been determined, but was absent from other Lactobacillus clades. To confirm the role of SpcB as the SpcA anchor and investigate the roles of these two proteins in surface properties of probiotic L. rhamnosus strains HN001 and GG, stable double-crossover mutations of these two genes were constructed. Binding assays to L. rhamnosus mutant cells confirmed dependence on SpcB in both GG and HN001 strains. Comparison of the wild-type and mutant surface properties suggested that SpcB in GG interferes with biofilm formation and aggregation, while it might contribute to the protective effect against TNFa-mediated disruption of the polarised Caco-2 cell monolayer integrity. Deletion of HN001 spcB or spcA had no effect on functions other than the SpcA binding. Our findings indicate that the roles of a surface protein can vary considerably among the strains of a species, requiring functional data to validate the bioinformatics-based hypotheses.
Keywords: Lactobacillus; Genetics; Probiotics; Lactobacillus rhamnosus